2018
DOI: 10.1111/jog.13854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local endometrial injury on in vitro fertilization/intracytoplasmic sperm injection outcomes: A systematic review and meta‐analysis

Abstract: Aim: Recent studies have revealed positive effects of endometrial injury on clinical pregnancy rates, but with inconsistent results. The aim of this meta-analysis was to assess the efficacy of endometrial injury (biopsy and/or hysteroscopy) as a potential treatment measure for implantation failure in the in vitro fertilization population. Methods: We searched in PubMed for studies comparing the efficacy of endometrial injury versus no intervention in women with at least one implantation failure. A random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…The majority of EI trials have found that EI in luteal phase increased the IVF success rate . The statement above has also been proved by several recent meta‐analysis studies . However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The majority of EI trials have found that EI in luteal phase increased the IVF success rate . The statement above has also been proved by several recent meta‐analysis studies . However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt .…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][5][6][7][8][9][10]26,27 The statement above has also been proved by several recent meta-analysis studies. 10,14 However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt. 15,16 Therefore, the clinical application of EI is still in controversial, especially for the frozen-thawed ET process due to the lack of evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, similar reviews were published. [9][10][11] Vitagliano et al showed improved reproductive outcomes in women with two or more previous failed cycles, with the greatest beneficial effect seen when double luteal EI was performed. 10 Van Hoogenhuijze et al found improved CPR but no improved LBR in women with at least two previous failed cycles, concluding that it is still unclear whether EI improves IVF outcomes.…”
mentioning
confidence: 99%